Plug-and-Play Higher-Order Process Integration. - Neubauer, Johannes; Steffen, Bernhard (Computer (00189162), 2013)
Unexpected hurdles in dealing with integration, variability, and interoperability in software development can be overcome using higher-order process integration. Even in its simplicity-oriented, tamed version, this approach fosters a powerful plug-and-play discipline, where processes and services are moved around like data.